2013
DOI: 10.3171/2013.1.focus133
|View full text |Cite
|
Sign up to set email alerts
|

Navigated transcranial magnetic stimulation for mapping the motor cortex in patients with rolandic brain tumors

Abstract: Object Navigated transcranial magnetic stimulation (nTMS) is a novel technology in the field of neurosurgery for noninvasive delineation of cortical functional topography. This study addresses the spatial accuracy and clinical usefulness of nTMS in brain tumor surgery in or near the motor cortex based on a systematic review of observational studies. Methods A systematic search retrieved 11 reports publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 21 publications
1
41
0
2
Order By: Relevance
“…Subject to further confirmation in large-scale studies, our mapping approach constitutes a valuable research tool for studies addressing non-invasive assessments of representational plasticity in M1 HAND since the linear shape-aligned mapping approach reliably captured the homuncular representation within-M1 HAND . The stereotactic guidance of coil placement also renders it possible to take into account dislocation or distortion of the shape of the central sulcus due to brain pathologies, for example in patients with peri-rolandic brain tumours or after motor stroke (Prashantha et al, 2013;Takahashi et al, 2013).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Subject to further confirmation in large-scale studies, our mapping approach constitutes a valuable research tool for studies addressing non-invasive assessments of representational plasticity in M1 HAND since the linear shape-aligned mapping approach reliably captured the homuncular representation within-M1 HAND . The stereotactic guidance of coil placement also renders it possible to take into account dislocation or distortion of the shape of the central sulcus due to brain pathologies, for example in patients with peri-rolandic brain tumours or after motor stroke (Prashantha et al, 2013;Takahashi et al, 2013).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…When coils are placed over the motor strips of cerebral cortex, just above the ears, TMS can be used to test the function of motor tracts extending from head to toe or from head to fingertips [8,10,11]. Such testing can be useful in monitoring the functional integrity of the spinal cord during neurosurgery, helping to avoid the dreaded complication of postoperative paralysis [3,12]. When coils are placed further forward over pre-frontal cortex TMS can be used treat psychic depression [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the use of navigated transcranial magnetic stimulation (nTMS) to map the motor cortex has been described. [14][15][16][17][18][19][20][21][22][23][24] In nTMS, conventional transcranial magnetic stimulation (TMS) is combined with sophisticated neuronavigation software that allows the navigation of every "stimulated" point in the cortex. 16,17,20,21 Several studies have already demonstrated the accuracy of this technique by comparing nTMS with functional MRI and direct cortical stimulation.…”
mentioning
confidence: 99%